Diverse Stakeholders of Tumor Metabolism: An Appraisal of the Emerging Approach of Multifaceted Metabolic Targeting by 3-Bromopyruvate - Yadav, Saveg; Pandey, Shrish Kumar; Goel, Yugal; Temre, Mithlesh Kumar; Singh, Sukh Mahendra (Frontiers in Pharmacology, 2019)
Malignant cells possess unique metabolic machinery to endure unobstructed cell survival. It comprises several levels of metabolic networking consisting of (1) Up-regulated expression of membrane-associated transporter proteins, facilitating unhindered uptake of substrates. (2) Up-regulated metabolic pathways for efficient substrate utilization. (3) pH and redox homeostasis, conducive for driving metabolism. (4) Tumor metabolism-dependent reconstitution of tumor growth promoting the external environment. (5) Up-regulated expression of receptors and signalling mediators. (6) Distinctive genetic and regulatory makeup to generate and sustain the rearranged metabolism. This feat is achieved by a ‘battery of molecular patrons,’ which acts in a highly cohesive and mutually coordinated manner to bestow immortality to neoplastic cells. Consequently, it is necessary to develop a multi-targeted therapeutic approach to achieve a formidable inhibition of the diverse arrays of tumor metabolism. Among the emerging agents capable of such multifaceted targeting of tumor metabolism, an alkylating agent designated 3-Bromopyruvate (3-BP) has gained immense research focus owing to its broad spectrum and specific antineoplastic action. 3-BP imparts inhibitory action on a variety of metabolic target molecules, including transporters, metabolic enzymes, and several other crucial stakeholders of tumor metabolism. Moreover, 3-BP also ushers a reconstitution of tumor microenvironment (TME), reversal of tumor acidosis and recuperative action on vital organs and systems of the tumor-bearing host. Studies have also been conducted to identify targets of 3-BP and its derivatives and characterization of target binding for further optimization. This review presents a brief discussion about the current state of knowledge of the aspects mentioned above of tumor metabolism and explores the novel aspects of the prospects of 3-BP as a safe and effective antineoplastic agent.